PENGARUH MODEL PROJECT BASED LEARNING PEMBELAJARAN MATEMATIKA MATERI PECAHAN TERHADAP HASIL BELAJAR SISWA KELAS IV SD - Nurafni Mangunsong; Putri Juwita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the effect of the Project Based Learning model on the mathematics learning outcomes of fourth-grade elementary school students. This is an experimental study using a one-group pre-test and post-test design. The method used is experimental with a quantitative approach. The study involved all students with a total learning outcome score of 1293.75. In the pre-test phase, the highest score obtained by students was 51, with an average score of 30. After the implementation of the Project Based Learning model, the maximum post-test score increased to 68. The analysis results showed that the significance value in the pre- test was 0.05, indicating no significant difference at the initial stage. However, the post-test result showed a significance value of 0.749, which is also greater than 0.05. This study illustrates that a project-based approach can be an alternative for improving the quality of learning in elementary schools.